Drug‐related teratogenic and pathologic causes of birth defects in a tertiary hospital in Southwestern Nigeria - Ifeanyichukwu Offor; Olufunsho Awodele; Kazeem A. Oshikoya (Wiley, 2019)
Abstract Birth defects are important causes of neonatal morbidity and mortality. A good understanding of the etiology is a vital step toward developing improved treatment and preventive strategies. We conducted an audit of medical records of newborns with birth abnormalities in a tertiary hospital over a 10‐year period, using a Pro forma designed to collect information on obstetric history, antenatal history, sociodemographics of parents, and the type of birth abnormality. Of the 180 medical records reviewed, female babies were 92 (51.1%) and male babies were 86 (47.8%). The mean age of the fathers was 38.2 + 6.2, and mothers 31.8 + 4.9. Majority 115 (63.9%) of the mothers had records of acute illnesses, and 23 (12.8%) chronic illnesses during pregnancy. Unspecified febrile illness 44 (38.3%), malaria 40 (34.8%), typhoid 8 (6.9%), hypertension 13 (56.5%), pregestational diabetes 4 (17.4%), and HIV 3 (13.0%) were the commonest maternal pathologies. Most of the documented birth abnormalities were Down's syndrome 34 (15.2%); congenital hydrocephalus 32 (14.3%); acyanotic congenital heart defect 30 (13.4%); deformity of the digits 26 (11.6%); and ventricular septal defect 20 (8.9%). The prevalence of maternal pathologies calls for concern, as these may be implicated in birth defects, therefore should be further investigated in future studies.